Objective: There were only few studies about the characteristic of vaginal pH among contraception user in Indonesia. This study aimed to determine the effect of contraception on vaginal pH among Indonesian women. Method: This study is a cross-sectional study. The target population was Indonesian women aged 15 - 50 years. The samples consisted of 492 people. Based on the method of contraception, subjects were grouped into 4 groups, subjects with combination hormonal contraceptives, progestin onl - Ocviyanti, Dwiana (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: There were only few studies about the characteristic of vaginal pH among contraception user in Indonesia. This study aimed to determine the effect of contraception on vaginal pH among Indonesian women. Method: This study is a cross-sectional study. The target population was Indonesian women aged 15 - 50 years. The samples consisted of 492 people. Based on the method of contraception, subjects were grouped into 4 groups, subjects with combination hormonal contraceptives, progestin only, condoms/IUDs, and subjects with no contraception or sterile. Vaginal acidity (pH) was examined by Dip- Stick (MerckÂ®). Result: The average age was 30.9 Â± 8.27. The methods of contraception the subjects used were combination hormonal contraception (18.0%), progestin-only (29.5%), condom/IUDs (5.1%) and no contraception/sterile (47.4%). Most subjects had vaginal pH